Upaya Meningkatkan Kemampuan Guru dalam Membuat Alat Peraga Pembelajaran Inovatif Melalui In House Training di SD Negeri 122/X Sungai Beras Semester Ganjil Tahun Ajaran 2022/2023 - Mulyadi Mulyadi (Journal on Education, 2022)
The background of this research is that the teacher's creativity has not yet been achieved in making innovative teaching aids because teachers do not understand the concepts, types, and criteria for innovative teaching aids. In addition, teachers also do not understand the content framework of innovative teaching aids. The purpose of this study was to obtain information discussing efforts to improve teachers' abilities in making innovative learning aids through in-house training at SD NEGERI 122/X Sungai Beras in the odd semester of the 2022/2023 academic year. This research is a school action research which consists of two cycles with each cycle following four stages, namely planning, implementing, observing, and reflecting. This research was conducted at SDN 122/X Sungai Beras in the odd semester of the 2022/2023 school year with 11 research subjects who were class teachers and subject teachers. Data collection techniques using observation, field notes and documentation. Data were analyzed using percentages and data reduction. Based on the results of the research and discussion, it can be concluded that through the implementation of in-house training (IHT) it can improve the ability of teachers to make innovative learning aids at SDN 122/X Sungai Beras in the odd semester of the 2022/2023 academic year. This can be seen from the increase in the teacher's ability from cycle to cycle with the act of giving rewards